2009
DOI: 10.4103/0028-3886.55606
|View full text |Cite
|
Sign up to set email alerts
|

Reactive changes of disc space and foreign body granuloma due to bone wax in lumbar spine

Abstract: Bone wax is a well-known agent used to prevent bleeding from the bone that can be used in different surgical procedures. Bone wax is a safe agent, but it may rarely lead to significant foreign body reactions. In this report, we present a patient who developed bone wax-related disc space foreign body granuloma following L4 total laminectomy, extremely rare complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Bone wax granulomas have been reported in mastoid tissue, the sternotomy site, the lumbar disc surgical site, the cerebellopontine angle, the subarachnoid space near the medulla oblongata, the femoral neck osteoplasty site, orbits, cranial defects, after tibial tubercle elevation surgery and after foot surgery [11]. In an anatomico-pathological study of 18 cadavers, it was reported that bone wax induces chronic inflammation and granuloma formation in the sternum postoperatively [12, 13]. Interestingly, the computed tomographic (CT) examination which is usually decided as the first diagnostic choice for the management of a patient with sternal dehiscence was unable to detect bone wax-related granuloma [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone wax granulomas have been reported in mastoid tissue, the sternotomy site, the lumbar disc surgical site, the cerebellopontine angle, the subarachnoid space near the medulla oblongata, the femoral neck osteoplasty site, orbits, cranial defects, after tibial tubercle elevation surgery and after foot surgery [11]. In an anatomico-pathological study of 18 cadavers, it was reported that bone wax induces chronic inflammation and granuloma formation in the sternum postoperatively [12, 13]. Interestingly, the computed tomographic (CT) examination which is usually decided as the first diagnostic choice for the management of a patient with sternal dehiscence was unable to detect bone wax-related granuloma [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…In an anatomico-pathological study of 18 cadavers, it was reported that bone wax induces chronic inflammation and granuloma formation in the sternum postoperatively [12, 13]. Interestingly, the computed tomographic (CT) examination which is usually decided as the first diagnostic choice for the management of a patient with sternal dehiscence was unable to detect bone wax-related granuloma [12, 13]. Thus magnetic resonance imaging (MRI) is recommended for evaluation of a complicated sternal wound.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that bone wax has deleterious consequences in bone healing and may contribute to postoperative complications [11][12][13][14][15][16][17] . However, bone wax has been used in craniofacial surgery because of its efficiency and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, cases such as infection as well as damages to surrounding tissues are also reported . Therefore the application of bone wax in bone surgery is under controversy currently . Research interests are moved to searching its potential alternatives.…”
Section: Introductionmentioning
confidence: 99%